Constraint-Induced Movement Therapy in Children Aged 5 to 9 Years With Cerebral Palsy. Issue 1 (2015) - Thompson, Ashley M.E.; Chow, Serena; Vey, Cathy; Lloyd, Meghann
<x xml:space="preserve">Abstract</x> Purpose: To examine the effectiveness of a modified form of constraint-induced movement therapy (mCIMT) in the context of a day camp model in 6 children aged 5–9 years with spastic hemiplegic cerebral palsy. Methods: Before, 1 week after, and 3 months after 9 consecutive days of mCIMT, participants were assessed using the Quality of Upper Extremity Skills Test (QUEST) and assessments of range of motion and grip strength. Caregiver perceptions were assessed using the Pediatric Evaluation of Disability Inventory (PEDI) and a parent questionnaire. Results: Significant improvements were observed on the "grasps" and "protective extension" subsections of the QUEST after the intervention. Increased social function was also observed as measured by the PEDI. All improvements were maintained at the 3-month follow-up assessment. Analysis of individual participants yielded additional information on clinically significant improvements as a result of the mCIMT intervention. Conclusions: The day camp model of mCIMT was effective in inducing lasting and meaningful changes in the children with hemiplegic cerebral palsy.